Editorial: Utopia and the right to dream - El Director (2013)
Everything indicates that "utopia" is a construction of the spirit, which responds to visions of ethical foundation that arouse active ideologies, stimulating and inspiring images of concrete actions, capable of modifying the existing reality. Utopia, when inscribed within certain coordinates of time and space, implies, on the one hand, the will to transcend the existing and present towards a better and possible world. On the other hand, it implies an evasion of the present and a critique of it, comparing it with what could be and with what we long for. Utopia, thus conceived, is a rational system that incorporates everything created in the material sphere, in the living reality and in the intangible reality.